Implementation of Core Competencies (Spiritual) in Online Learning in Elementary Schools: Implementasi Kompetensi Inti (Spiritual) dalam Pembelajaran Daring di Sekolah Dasar - Indrawan, Lendik Dicky; Rezania, Vanda (Indonesian Journal of Education Methods Development, 2022)
The purpose of this research is to describe the implementation of core competencies (spiritual) in online learning during the Covid-19 pandemic in class IV SDN Cemengkalang and to describe indicators of spiritual competence that have been implemented online during the Covid-19 pandemic in class IV SDN Cemengkalang. Data analysis was carried out with data reduction, data display, and conclusion drawing/verification. The results showed that the implementation of spiritual competence in online learning during the Covid-19 pandemic in grade IV SDN Cemengkalang was known from several activities, including: a) Grade IV students at SDN Cemengkalang did not forget to continue to worship in a timely manner even when they were working on assignments. given by the teacher; b) Before and after the lesson, the fourth grade students of SDN Cemengkalang always pray for the smooth running of teaching and learning activities and so that the knowledge gained is beneficial for students; c) Fourth grade students at SDN Cemengkalang always answer the greetings spoken by the teacher before and after lessons; d) Grade IV students of SDN Cemengkalang are always grateful for having been given physical and spiritual health so that they are able to follow the delivery of subject matter via zoom and do assignments in the classroom application. The results also show that the indicators of spiritual competence that have been implemented online during the Covid-19 pandemic in grade IV SDN Cemengkalang are indicators of accepting and carrying out their religious teachings through praying before and after doing something, performing worship on time, greeting the teacher. and always grateful for the blessings and gifts of God Almighty for having been given health so that they can take part in learning activities even though they are online and can do their jobs well.